Agrohomeopathic preparations for the modulation of Plasmodiophora brassicae in cauliflower and cabbage under greenhouse conditions - Rodríguez-García, Daniela (2026)
Introduction. Clubroot, caused by Plasmodiophora brassicae, is one of the most limiting diseases affecting cauliflower (Brassica oleracea var. botrytis) and cabbage (B. oleracea var. capitata), due to the pathogen’s long-term soil persistence and the severity of root symptoms. Objective. The objective of this study was to evaluate agrohomeopathic preparations on plant growth and disease severity under greenhouse conditions. Materials and methods. A completely randomized design was established with 14 treatments and 10 replicates per treatment, including three agrohomeopathic products (Arsenicum album, Sulphur, and Phosphorus), two application frequencies (every 7 and 15 days), and two soil conditions (sterilized and non-sterilized), all inoculated with P. brassicae. Results. Evaluated variables included leaf and root length, fresh leaf and root weight, leaf dry weight, and disease severity using an ordinal scale. Significant differences (p ≤ 0.05) were observed among treatments for all variables. Weekly application of Sulphur in sterile soil resulted in the highest growth responses, with increases between 98 and 116% in leaf length and reductions exceeding 70% in the probability of belonging to the highest severity categories compared to the control. Conclusions. Overall, the evaluated preparations demonstrated the ability to enhance vegetative growth and reduce symptom expression under controlled conditions, suggesting their potential as complementary tools within sustainable agricultural production systems.